Sampul Depan, Daftar Isi, Kata Pengantar - Depan, Sampul; Isi, Daftar; Pengantar, Kata (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2023)
Sampul Depan, Daftar Isi, Kata Pengantar